Effect of Fusarium wilt disease on varied Chickpea germplasm and its management - Anwar, Rida; Zeshan, Muhammad Ahmad; Ghani, Muhammad Usman; Ali, Amjad; Iftikhar, Yasir; Bakhsh, Allah (Journal of Pure and Applied Agriculture, 2023)
Chickpea wilt, caused by Fusarium oxysporum f. sp. ciceris (Foc) is the most common soil-borne fungus that affects chickpea plants and destroys crops up to 100% in favorable conditions. In the current research, seeds of 12 chickpea varieties were obtained from the Ayub Agricultural Research Institute, Faisalabad (Pakistan). The varieties were sown in augmented design and screened against the Fusarium wilt under field conditions. The symptomatic samples were collected and pathogenicity tests performed for the confirmation of pathogen. The food poisoning technique was used to check the effectiveness of 3 fungicides (Capnazole, Flumax and Mixtin) at concentrations (75ppm, 150ppm, 300ppm) in-vitro and the most effective concentration was used in field experiments. In management experiment, 3 chickpea varieties (Bittal-110, Noor-2013 and Noor-2019) were sown in a randomized complete block design (RCBD) and a combination of nutrients and chemicals viz; T1 (ZnSO4+ MnSO4+Boric acid+ Capnazole), T2 (ZnSO4+ MnSO4+Boric acid+ Flumax), and T3 (ZnSO4+ MnSO4+Boric acid+ Mixtin) were used by foliar spray methods. The data of environmental variables was collected from the weather observatory and correlated with disease. The results revealed that minimum disease incidence (15.33%) was recorded on AD-08 and maximum disease incidence (68.33%) was recorded on NF1-1733. The maximum mycelial growth inhibition of Foc was recorded at concentration 300 ppm in all 3 fungicides while Capnazole was the most effective with 65.68% inhibition followed by Flumax (60.48%) and Mixtin (36.89%). Under field conditions, T1 (ZS+MS+BA+Capnazole) was the most effective in controlling wilt disease (33.22%) followed by T2 (ZS+MS+BA+Flumax), and T3 (ZS+MS+BA+Mixtin). There was a significantly positive correlation between maximum temperature, minimum temperature, wind speed, rainfall and the negative correlation between relative humidity for disease incidence in present study. The study would provide a base for the sustainable management of wilt disease of chickpea under various agro climatic zones. © 2022 Department of Agricultural Sciences, AIOU